2021
DOI: 10.3389/fmed.2021.791716
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Plasminogen Activator Receptor (suPAR) Independently Predicts Severity and Length of Hospitalisation in Patients With COVID-19

Abstract: Background: Efficient healthcare based on prognostic variables in hospitalised patients with COVID-19 could reduce the risk of complications and death. Recently, soluble urokinase Plasminogen Activator Receptor (suPAR) was shown to predict respiratory failure, kidney injury, and clinical outcome in patients with SARS-CoV-2 infection. The aim of this study was to investigate the value of suPAR as a prognostic tool, in comparison with other variables, regarding disease severity and length of hospital stay in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 66 publications
3
46
0
Order By: Relevance
“…These have been shown to have a positive correlation with the development of pulmonary lesions during early COVID-19, and consequently with severe COVID-19 and related respiratory complications [70, 71]. We recently found an association of soluble urokinase Plasminogen Activator Receptor with COVID-19 severity, and length of hospitalization [72]. Additionally, lymphopenia was observed in many of the COVID-19 patients in our cohort at inclusion (i.e., at hospitalization), and is a common clinical observation [7376] that may likely be attributed to the cells relocating or consequently dying at this stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These have been shown to have a positive correlation with the development of pulmonary lesions during early COVID-19, and consequently with severe COVID-19 and related respiratory complications [70, 71]. We recently found an association of soluble urokinase Plasminogen Activator Receptor with COVID-19 severity, and length of hospitalization [72]. Additionally, lymphopenia was observed in many of the COVID-19 patients in our cohort at inclusion (i.e., at hospitalization), and is a common clinical observation [7376] that may likely be attributed to the cells relocating or consequently dying at this stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Examples from non-neoplastic pathological conditions associated to enhanced SuPAR expression include the focal segmental glomerulosclerosis, a disease in which high SuPAR plasma levels predict disease progression to end-stage renal failure ( Winnicki et al, 2019 ). It was recently reported that high levels of blood SuPAR predict severe/critical Covid-19 disease and are associated with length of hospital stay ( Enocson et al, 2021 ).…”
Section: Diagnostic and Terapeutic Aspectsmentioning
confidence: 99%
“…This pilot study is a part of a prospective, observational cohort study described elsewhere [ 18 ], implemented during August 2020 to May 2021, and involving hospitalized adult patients with COVID-19.…”
Section: Methodsmentioning
confidence: 99%